Characteristic differences in essential oil composition of six Zanthoxylum bungeanum Maxim. (Rutaceae) cultivars and their biological significance - Liu, Shu-ming (Zhejiang University Press, 2017)

(untitled) (J Zhejiang Univ Sci B)
Great variations have been found in composition and content of the essential oil of Zanthoxylum bungeanum Maxim. (Rutaceae), resulting from various factors such as harvest time, drying and extraction methods (Huang et al., 2006; Shao et al., 2013), solvent and herbal parts used (Zhang, 1996; Cao and Zhang, 2010; Wang et al., 2011). However, in terms of artificial introduction and cultivation, there is little research on the chemical composition of essential oil extracted from Z. bungeanum Maxim. cultivars, which have been introduced from different origins. In this study, the composition and content of essential oil from six cultivars (I–VI) have been investigated. They were introduced and cultivated for 11 years in the same cultivation conditions. Cultivars were as followings: Qin’an (I) cultivar originally introduced from Qin’an City in Gansu Province; Dahongpao A (II) from She County in Hebei Province; Dahongpao B (III) from Fuping County; Dahongpao C (IV) from Tongchuan City; Meifengjiao (V) from Feng County; and, Shizitou (VI) from Hancheng City, in Shaanxi Province, China. This research is expected to provide a theoretical basis for further introduction, cultivation, and commercial development of Z. bungeanum Maxim.